Enhancing paediatric palliative care: A rapid review to inform continued development of care for children with life‐limiting conditions. (14th December 2021) - Ekberg, Stuart; Bowers, Alison; Bradford, Natalie; Ekberg, Katie; Rolfe, Melanie; Elvidge, Norah; Cook, Rebecca; Roberts, Sara‐Jane; Howard, Christine; Agar, Meera; Deleuil, Renee; Fleming, Sara; et al.
Abstract : Aim: Following the establishment of paediatric palliative care services over recent decades, this study sought to identify information to inform future policy and practice. Methods: A rapid review using thematic synthesis was conducted to synthesise existing information about improving paediatric palliative care. Information was extracted in relation to key areas for investment and change: quality, access, advance care planning, skills, research, collaboration and community awareness. Results: A total of 2228 literature sources were screened, with 369 included. Synthesised information identified clear ways to improve quality of care, access to care, advance care planning, and research and data collection. The synthesis identified knowledge gaps in understanding how to improve skills in paediatric palliative care, collaboration across Australian jurisdictions and community awareness. Conclusions: The findings of this review bring together information from a vast range of sources to provide action‐oriented information to target investment and change in paediatric palliative care over the coming decades.